Fabrication of Pd/CuFe2O4 hybrid nanowires: a heterogeneous catalyst for Heck couplings. (4th January 2018) - Lakshminarayana, B.; Mahendar, L.; Ghosal, P.; Sreedhar, B.; Satyanarayana, G.; Subrahmanyam, Ch.
Abstract : Hybrid heterogeneous catalyst, palladium(0) on copper ferrite nanowires has been synthesized and characterized. Significantly, this catalyst for the first time employed in the Jeffrey Heck reaction between iodo-arenes and allylic alcohols. Abstract : The development of environmentally benign transformations is indispensable in organic synthesis. Herein, a hybrid heterogeneous catalyst, palladium(0) on copper ferrite nanowires, has been synthesized, characterized, and for the first time, employed in the Jeffrey Heck reaction between iodoarenes and allylic alcohols, and good to excellent yields have been obtained. In addition, the catalyst was found to be suitable for the usual Heck coupling. The nanocatalyst was recovered and reused up-to multiple runs without any noticeable loss of its catalytic activity.